Ageing Labour Forces - Promises and Prospects - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2008)
Ageing Labour Forces -- Promises and Prospects, edited by Philip Taylor, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Cultural change; International; Labor Unions; Labor force; Older workers; Public policy; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z